1988
DOI: 10.1007/bf00339605
|View full text |Cite
|
Sign up to set email alerts
|

Non-mendelian inheritance of mitochondrial DNA and ribosomal DNA in the myxomycete, Didymium iridis

Abstract: The inheritance of both the mitochondrial DNA (mtDNA) and the nuclear-encoded extrachromosomal ribosomal DNA (rDNA) has been studied in the myxomycete, Didymium iridis, by DNA-DNA hybridization of labeled probes to total DNA at various stages of the life cycle. Both the mtDNA and rDNA populations rapidly become homogeneous in individuals, but there is a qualitative difference in the patterns of inheritance of these two molecules. One parental rDNA type was preferentially inherited in all crosses; selective rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…In D. iridis, the inheritance mode of mitochondria has been analyzed. The results showed that the inheritance mode of mitochondria is predominantly uniparental (Silliker and Collins 1988;Silliker et al 2002, Sheer andSilliker 2006). The uniparental inheritance of organelle is a widely conserved phenomenon in many organisms, and as the 2 Myxomycetes P. polycephalum and D. iridis are relatively closely related species, it could be expected that they possess the same mechanism for the uniparental inheritance of mitochondria.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In D. iridis, the inheritance mode of mitochondria has been analyzed. The results showed that the inheritance mode of mitochondria is predominantly uniparental (Silliker and Collins 1988;Silliker et al 2002, Sheer andSilliker 2006). The uniparental inheritance of organelle is a widely conserved phenomenon in many organisms, and as the 2 Myxomycetes P. polycephalum and D. iridis are relatively closely related species, it could be expected that they possess the same mechanism for the uniparental inheritance of mitochondria.…”
Section: Discussionmentioning
confidence: 93%
“…In this study, we observed the behavior of mtDNA during the mating of Myxomycete D. iridis, to investigate that selective disappearance of mtDNA is a conserved mechanism for the uniparental inheritance of mitochondria, at least in Myxomycetes. The inheritance mode of mtDNA has already been reported in D. iridis, and it is strictly uniparental (Silliker and Collins 1988, Silliker et al 2002, Sheer and Silliker 2006. The life cycle of D. iridis includes 2 distinct vegetative forms: the haploid myxamoeba and the diploid plasmodium.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Because no cell division takes place, mitochondrial segregation does not occur. However, uniparental inheritance of mitochondria has also been reported in the isogamous protists P. polycephalum (Kawano et al 1987a, b;Kawano and Kuroiwa 1989;Meland et al 1991) and D. iridis (Silliker and Collins 1988;Silliker et al 2002). Loss of paternal mitochondria is presumed to happen at an early stage of zygote differentiation despite gametes of equal size being involved, and the zygote develops without Fig.…”
Section: Maternal Inheritance and The Selective Digestion Hypothesis:mentioning
confidence: 89%
“…Furthermore, the fact that both parental rDNA types are present at the same time, as shown by the polymorphism of the intronindependent marker, strongly favours intron mobility. In a previous study, Silliker and Collins (1988) analysed the inheritance of extrachromosomal rDNAs in D. iridis. They used two parental strains (Pan2-16 and Hon1-2) similar to those presented in this work, and found that the Pan2-16 parental rDNA type was preferentially inherited in all crosses.…”
Section: Discussionmentioning
confidence: 99%